STRATEGI PEMASARAN USAHA BUNGA PAPAN DI KOTA PEKANBARU (Studi Kasus pada Usaha Bunga Papan Valentine Florist) - Sri Indayah Handayani; Eliza '; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to identify the marketing mix florist board, identify internal factors (strengths and weaknesses) and external factors (opportunities and threats) that faced, developed and recommend appropiate alternative marketing strategies. The research was conducted in June 2013 until the end. The sampling method used in this research is a case study in the Valentine Florist’s florist board business. The data were analyzed descriptively. Results showed interest board products offered by various designs and sizes, ranging from size to size 2mx3m 2mx12m and can be combined using fresh flowers. Rental price charged to the consumer products amounted to Rp 100,000 rupiah/board. Product distribution channels carried by employers are only one level. Promotion is done is through the division enterpreneur cards and banners installed on each foot flower display board. Alternative marketing strategies based on the SWOT matrix can be chosen that maintain product image by improving the quality of products and services and maintain consumer trust, maintain exiting markets and seek new market opportunities, utilizing the media campaign to seize market opportunities, offering derivative products of interest apart from board interest to consumers, promote products to consumers continuouly.   Keywords: Florist Board Business, Marketing Mix and Marketing Strategy